2017
DOI: 10.5006/2247
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of Anodic Hydrogen on High Purity Magnesium in Acidic Buffer Solution

Abstract: Hydrogen evolution (HE) on anodically polarized Mg, commonly referred to as Negative Difference Effect, was studied by galvanodynamic measurements coupled with real-time gravimetric H 2 volume collection, the Scanning Vibrating Electrode Technique and potentiodynamic polarization experiments. High purity Mg (99.96% Mg) electrodes were studied in chloride-free 0.1 M citric acid solution buffered at pH with the aim of determining the source of anodic HE and the role of the corrosion film on the process. In such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 32 publications
0
27
0
Order By: Relevance
“…Since the development of the gravimetric method for HE, GDP measurements have shown to reliably monitor the real-time evolution of H 2 from a Mg surface. Using GDP instead of GSP allows for an easy determination of the HE current density in a single GDP measurement by interpolation in a HE current density vs. applied current density plot [16] (see Figure 7). This has shown to be particularly useful when short timescales are needed or when limited amount of material is available and a large range current densities need to be applied.…”
Section: Galvanodynamic Polarization (Gdp) and Galvanostatic Polarizamentioning
confidence: 99%
See 1 more Smart Citation
“…Since the development of the gravimetric method for HE, GDP measurements have shown to reliably monitor the real-time evolution of H 2 from a Mg surface. Using GDP instead of GSP allows for an easy determination of the HE current density in a single GDP measurement by interpolation in a HE current density vs. applied current density plot [16] (see Figure 7). This has shown to be particularly useful when short timescales are needed or when limited amount of material is available and a large range current densities need to be applied.…”
Section: Galvanodynamic Polarization (Gdp) and Galvanostatic Polarizamentioning
confidence: 99%
“…These authors also have used SVET for studying the behavior of a range of potential anionic inhibitors, selected on the basis of their ability to form insoluble precipitates with aqueous Mg 2+ ions [46]. Their results using SVET for investigating the source of hydrogen evolution from high purity Mg anodically polarized are also significant [14,16,47].…”
Section: Scanning Electrochemical Techniquesmentioning
confidence: 99%
“…The well-known increase of the HER rate under anodic polarization of Mg seems to be in contradiction with the kinetic models of charge transfer electrochemical reactions (Butler-Volmer equation), predicting that the cathodic current should decrease exponentially with increasing anodic potential. This phenomenon called "the negative difference effect" (NDE) [9][10][11][12][13][14][15][16] and more recently "the anodic hydrogen evolution" process 17,18 has been also observed for other metals than Mg such as Al, Li. [19][20][21][22] Despite the abundant literature on Mg corrosion and many models of Mg corrosion (such as: the formation of Mg(I) as an intermediate product, 23,24 the formation and breakdown of the partially protective film, 11,[25][26][27] the formation of hydride intermediates, [28][29][30][31][32] or the catalytic activity of alloying elements and noble metal impurities) 22,33,34 the mechanisms still remain unclear.…”
mentioning
confidence: 99%
“…[16][17][18]22 However, the ability of the sub-surface Al distribution and any associated Al enrichment layer to alter the surface film to avoid cathodic activation has not been investigated in a unified context. The scanning vibrating electrode (SVET) technique has eloquently revealed that breakdown of Mg 23,24 and single phase Mg-Al alloys [25][26][27] in NaCl (aq) electrolytes involves laterally-spreading focal anodes that leave behind cathodically-activated corrosion products. Thus, identifying microstructural features that can alter surface films to avoid cathodic activation is desirable from a corrosion performance perspective.…”
Section: Introductionmentioning
confidence: 99%